Numerical flow simulations of the shear stress forces arising in filtration slits during glomerular filtration in rat kidney: basic research - Fuhrmann, Alexander; Pritz, Balazs; Endlich, Karlhans; Kriz, Wilhelm (Journal of the American Society of Nephrology, 2025)
Key Points Computational fluid dynamics were applied to estimate the shear stress challenge to the filtration barrier during glomerular filtration in rats. Shear forces were especially relevant in pathologic situations where they contribute to the loss of viable podocytes. Background The flow dynamic forces during glomerular filtration challenging the fixation of podocytes to the glomerular basement membrane (GBM) are insufficiently understood. Methods Numerical flow simulations were used to estimate these forces in the rat kidney. Simulations were run with a three-dimensional (3D) model of the slit diaphragm as a zipper structure according to Rodewald and Karnovsky. The GBM was modeled as a porous medium. Results Filtrate flow exerted a mean wall shear stress of 39 Pa with a maximum of 152 Pa on the plasma membrane of foot processes and up to 250 Pa on internal surfaces of the slit diaphragm. The slit diaphragm accounted for 25% of the hydrodynamic resistance of the glomerular filtration barrier. Based on the results of the 3D model, we developed a two-dimensional (2D) model that allowed us to perform extensive parameter variations. Reducing the filtration slit width from 40 to 30 nm almost doubled wall shear stress. Furthermore, increasing filtrate flow velocity by 50% increased wall shear stress by 47%. When increasing the viscous resistance of the slit diaphragm, the pressure drop across the slit diaphragm increased to intolerably high values. A lower viscous resistance of the slit diaphragm than that of the GBM accounted for a gradual pressure decline along the filtration barrier. The subpodocyte space tempered these challenges in circumscribed areas of filtration surface but had only a marginal impact on overall forces. Conclusions The filtration barrier experiences high levels of shear and pressure stress accounting for the detachment of injured but viable podocytes from the GBM—a hallmark in many glomerular diseases.